Dark Clouds Ahead? Anecdotal evidence for an illegal live trade in Sunda Neofelis diardi and Indochinese N. nebulosa Clouded Leopards (Mammalia: Carnivora: Felidae) - Anthony J. Giordano; Leah Winstead; Muhammad Ali Imron; Rustam; Jephte Sompud; Jayaraj Vijaya Kumaran; Kurtis Jai-Chyi Pei (Wildlife Informaton Liaison Development Society, 2023)
The Sunda Clouded Leopard (Neofelis diardi) and Indochinese Clouded Leopard (N. nebulosa) are medium-sized felids native to tropical south and southeast Asia. In 2019, we began investigating the trade in Clouded Leopards and their parts in Asia. This was partly inspired by social media posts of an apparent pet Sunda Clouded Leopard. Investigations continued with respect to how and where Clouded Leopards are sold on social media and other digital platforms. We discovered several social media posts and local language news articles, that we believe are indicative of an illegal live trade in Sunda Clouded Leopards in Indonesia. While fewer instances of trade in Indochinese Clouded Leopards have been discovered thus far, patterns of trade in other large felids and small carnivores in the region, particularly as influenced by social media, may have implications for future live trade in Indochinese Clouded Leopards and increased trade in Sunda Clouded Leopards. We recommend that additional international attention and investment of resources, including local, national, and international law enforcement activities, focus their efforts on the growing trade in Clouded Leopards.